Influence of Pinning Effects on the Electrochemical Formation of Silver Patterns in Agarose-Containing Sols and Gels - Pasquale, Miguel Ángel (2005)
The formation of silver patterns via electrolysis from aqueous silver sulfate + x% w/v agarose sol and gel media, with and without supporting electrolyte, in a quasi-two-dimensional (2D) cylindrical cell at room temperature, is utilized as a reference system to investigate the complexity of pinning effects. From pattern morphology and electrochemical data, both delocalized and localized pinning in the bulk dominate the drift of the growth front, depending on the concentration of agarose in the heterogeneous media. Delocalized pinning results from mobile, small agarose aggregates at the growth front and from their accumulation by the front drift. For gels, localized pinning comes from their own percolated structure. A depinning/pinning transition is observed in going from sols to gels. The relative contribution of diffusion and advection in mass-transport-controlled silver electrodeposition depends on the plating bath composition. On the other hand, silver ion attachment to the cathode appears to be interfered with by some screening caused by weakly adsorbed, mobile agarose aggregates at the metal surface without slowing down the rate of the electron-transfer step at the cathode. Their relative contribution of a delocalized, localized pinning and screening effect to a great extent determines the morphology and transition in the growth mode of silver patterns in both media. The analysis of charge and current transients and the corresponding silver pattern morphologies for open and dense radial patterns is made. Results are qualitatively simulated with a novel, rather simple cellular automaton algorithm.